Interaction among upper intermediate ESL/EFL learners engaged in collaborative writing - Pathinathan, Santini (2013)
Learning to write collaboratively is important to develop team spirit as more workplace writing involves teamwork. Although it is known that collaborative writing could help students produce better written work, little attention has been paid to how the role of a group member affects interaction during collaboration. This study identified the roles of the participants during collaboration and the effects on their interactions. It also investigated the different types of conflict that occur during collaborative writing and how collaboration improved ESL / EFL learners’ writing skills. Collaborative writing is grounded on socio-cultural theory in second language learning. Vygotsky (1978) claims, that social interaction plays a fundamental role in the development of cognition. This can be seen when the “less expert (novice) participant can appropriate and internalise knowledge or skill which is collaboratively developed in the course of the interaction” (p. 84). Therefore, this study used sociocultural theory as the theoretical framework. The study used a qualitative and quantitative research design. Data was collected from three case study groups which comprise four members of different cultural backgrounds. The participants were assigned to write an individual argumentative essay as a pre-test before collaboration and an individual argumentative essay as a post-test after the collaboration. They also participated in three collaborative writing sessions over seven weeks. After each collaborative session, the participants were interviewed individually. The interactions during collaboration was video and audio recorded. Participants also jotted down their experiences and perceptions on collaboration in journals. The audio recordings were transcribed verbatim. The transcriptions were analysed by selecting significant episodes which reveal how the roles affect interaction during collaboration. Besides that, significant episodes that reveal the different types conflict that the groups face were also identified. The pre-test and post-test were compared to identify how collaboration among ESL / EFL learners improve their writing skills. Data from the interviews and journal were used for triangulation. The findings reveal that group members may exchange roles throughout the tasks and it has a considerable impact on their interaction as they strive to complete the tasks given. It also shows that familiarity among group members is crucial for successful collaboration. The participants found that through collaboration they became more confident writers and developed idea generation skills besides learning from each other,thus improving their writing. The study also shows that the success of collaborative writing depends very much on how conflict is handled and resolved among the members. Several implications and recommendation have been drawn regarding the usage of collaborative writing in ESL / EFL classrooms based on the findings of this study.